Strategies for automotive filter component manufacturers towards electric vehicles era in Indonesia - Rahmat Nurcahyo; Hikari Nurhadi; Muhammad Habiburrahman (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2021)
In conventional cars, a filter is one of the automotive components directly associated to the internal combustion engine (ICE) and will be disappeared if electric vehicles dominate. By carrying out a case study approach to filter manufacturers and formulating problems with a strategic management approach and SWOT analysis, the results show that filter manufacturers can still take advantage of opportunities by using their existing internal strengths; therefore, an alternative strategy is to implement aggressive or diversification strategies in the future.